Antiviral effects of antisense morpholino oligomers in murine coronavirus infection models - Burrer, Renaud; Neuman, Benjamin W; Ting, Joey P C; Stein, David A; Moulton, Hong M; Iversen, Patrick L; Kuhn, Peter; Buchmeier, Michael J (Journal of virology, 2007)
The recent emergence of novel pathogenic human and animal coronaviruses has highlighted the need for antiviral therapies that are effective against a spectrum of these viruses. We have used several strains of murine hepatitis virus (MHV) in cell culture and in vivo in mouse models to investigate the antiviral characteristics of peptide-conjugated antisense phosphorodiamidate morpholino oligomers (P-PMOs). Ten P-PMOs directed against various target sites in the viral genome were tested in cell culture, and one of these (5TERM), which was complementary to the 5' terminus of the genomic RNA, was effective against six strains of MHV. Further studies were carried out with various arginine-rich peptides conjugated to the 5TERM PMO sequence in order to evaluate efficacy and toxicity and thereby select candidates for in vivo testing. In uninfected mice, prolonged P-PMO treatment did not result in weight loss or detectable histopathologic changes. 5TERM P-PMO treatment reduced viral titers in target organs and protected mice against virus-induced tissue damage. Prophylactic 5TERM P-PMO treatment decreased the amount of weight loss associated with infection under most experimental conditions. Treatment also prolonged survival in two lethal challenge models. In some cases of high-dose viral inoculation followed by delayed treatment, 5TERM P-PMO treatment was not protective and increased morbidity in the treated group, suggesting that P-PMO may cause toxic effects in diseased mice that were not apparent in the uninfected animals. However, the strong antiviral effect observed suggests that with further development, P-PMO may provide an effective therapeutic approach against a broad range of coronavirus infections.